Experience of Paediatric Acute Lymphoblastic Leukemia Service in A Newly Established Haemato-Oncology Center in Bangladesh: Opportunities and Challenges - Sonia, Sheikh Farjana; Mishra, Avijeet Kumar; Gogoi, Manash Pratim; Sultana, Azmeri; Afroze, Sharmin (Dhaka Shishu (Children) Hospital Journal, 2022)
Background: Acute lymphoblastic leukemia (ALL) is the most common childhood malignancy and its modern management is complex. We are reporting early experience of establishing a paediatric ALL service in a multidisciplinary paediatric hospital in Bangladesh. Methods: This is a retrospective review of children below 18 years of age with confirmed diagnosis of ALL from July 2020 to June 2021 in Dr. M R Khan Shishu Hospital and ICH, Dhaka, Bangladesh, who received treatment adapted from the standard arm of ICICLE (Indian Childhood Collaborative Leukemia Group) protocol. Data were collected which included demographic, clinical, laboratory features of all patients at the time of presentation and also morbidities and outcome during all phases of chemotherapy. Analysis was done using descriptive statistics. Results: Of 51 patients, 16 were newly diagnosed patients, 32 received continuation care and 3 had relapsed disease. Treatment was initiated in 12 (75%) of 16 patients with newly-diagnosed ALL. Median age was three years, 50% were girls, one had TALL and 5 (42%) had high presentation leucocyte count (³50,000/mm3). Complete cytogenetic testing was available for one patient alone, no patient had Ph+ ALL. Eleven (92%) showed good prednisolone response. All nine patients who completed the induction phase achieved morphological remission, with high minimal residual disease (³0·01%) in two (22%). At last follow-up (30-06-2021), two patients were midway through induction, two died from sepsis (one each in Induction and Consolidation, both high risk ALL) and eight (67%) are alive in remission, on treatment 2-12 months from diagnosis. Continuation care included intrathecal treatments (n=119) and vincristine-corticosteroid pulses (n=53); 94% patient remained in complete remission, while two (6%) relapsed during the course of treatment. Conclusion: Risk-stratified ALL treatment is feasible in a newly established resource limited setting but limited by availability of high-quality diagnostics, specifically cytogenetics. Our study revealed that, during intensive phase approximately two-third children and during maintenance phase majority of children remained in complete remission. DS (Child) H J 2021; 37(2): 116-122